Plane Ticket Price Dispersion in the Online Selling System in Poland - Tomasz Stanisław Szopiński; Robert Nowacki (Contemporary Economics, 2014)
Many authors have studied the influence exerted by tourism on the economy. Today, Information and Communication Technologies (ICT) are an important factor influencing competitiveness in the tourism sector and consumers' decision-making concerning tourism purchases. Along with the expansion of the European Union, the revolution in passenger air transportation has spread over new member states in Central and Eastern Europe, including Poland. The authors of this study analyzed ticket prices on Internet websites that aggregate offers from different carriers and on the websites managed by the carriers themselves, specifically studying offers for the most popular flight connections from F. Chopin airport in Warsaw to London, Frankfurt, Munich, and Paris. For each connection, the study examined flights operated by the Polish carrier, i.e., LOT Polish Airlines, and by a carrier originating from a destination country. The analysis of the particular coefficients illustrating the price dispersion for each flight operated by a foreign carrier in comparison to the offer from LOT Polish Airlines points to the conclusion that the tickets offered by the latter were marked by a much narrower price dispersion in contrast to the connections offered by foreign carriers on the same route.
Keywords: D12; F12; L81; 330; e-tourism; ICT; airline ticket price; price dispersion; price discrimination; price competitiveness